Proceedings of the 4th International Conference on Innovation in Education, Science and Culture, ICIESC 2022, 11 October 2022, 2022
DOI: 10.4108/eai.11-10-2022.2325297
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Leading Commodities on The Sumatra Island

Abstract: Commodity identification in each province is required so that business sector development is more efficient, adds value, and produces optimal results. The purpose of this research is to examine the leading commodities and provinces on the Sumatra Island that have a comparative advantage in the agriculture, forestry, and fishery sectors. PDB, PDRB, and Sub-Sector PDRB in 2015-2021 data from agencies such as BPS, BI, and Bappenas are used, with the Location Quotient (LQ) and Revealed Comparative Advantage (RCA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…The period of data used in this study is too narrow, only from 2 nd quarter of 2019 to 2 nd quarter of 2020. (Mardiyah et al, 2022) found similar results where Mining and Quarrying, Processing Industry, Water Supply, Waste Management, Waste and Recycling, and Construction are leading sectors in Riau Islands.…”
Section: Theoritical Reviewsupporting
confidence: 55%
“…The period of data used in this study is too narrow, only from 2 nd quarter of 2019 to 2 nd quarter of 2020. (Mardiyah et al, 2022) found similar results where Mining and Quarrying, Processing Industry, Water Supply, Waste Management, Waste and Recycling, and Construction are leading sectors in Riau Islands.…”
Section: Theoritical Reviewsupporting
confidence: 55%